Revisiting the theory of income and wealth distribution: A comparative study in western and Islamic economic theories - Mohd Mazlan, Ain Nur Nadhirah; Akbar, Mohamed Aslam (EKONIS-UKM Research Centre for Islamic Economics and Finance, 2021)
The theory of distribution has undergone a long series of formation and reformation since the classical economics era until the modern development of Islamic economics. It is one of the crucial concepts in economics as it deals with determining the nation's level of inequality and poverty. Classical and neoclassical economists have contributed to the mainstream concept of distribution today. Scholars like Alfred Marshall, John Bates Clark, and John Rawl will come into pictures describing the 'extended version' of the theory of marginal productivity by Adam Smith and David Ricardo. In the realm of Islamic economic thought, scholars like Baqir al-Sadr, Monzer Kahf and Shafinah Rahim attempt to bridge the knowledge with the Islamic approach with references to Shariah ruling. Some Islamic critique to the conventional theory of distribution was presented to search for the loopholes and enable room for improvement. The most recent development on the model of distributive justice and the accentuation role of al-Hisbah was proposed to develop a more conducive economic environment with a better distribution system.